Natural products for the treatment and management of diabetes mellitus in Zimbabwe-a review - Usai, Remigio; Majoni, Stephen; Rwere, Freeborn (Frontiers in Pharmacology, 2022)
Use of medicinal plants and herbs in the treatment and management of diseases, including diabetes mellitus and its complications remains an integral part of African tradition. In Zimbabwe, nearly one million people are living with diabetes mellitus. The prevalence of diabetes mellitus in Zimbabwe is increasing every year due to lifestyle changes, and has accelerated the use of traditional medicines for its treatment and management in urban areas. In addition, the high cost of modern medicine has led many people in rural parts of Zimbabwe to rely on herbal plant medicine for the treatment of diabetes mellitus and its complications. This review highlights a number of studies carried out to evaluate the antidiabetic properties of indigenous plants found in Zimbabwe with the goal of treating diabetes mellitus. Further, we discuss the mechanism of action of various plant extracts in the treatment and management of diabetes mellitus. Together, this review article can open pathways leading to discovery of new plant derived medicines and regularization of use of crude plant remedies to treat diabetes mellitus by the Zimbabwean government and others across Africa.